2018
DOI: 10.1155/2018/4618716
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone Treatment for Neuronal Deficits: A Histological and MEMRI Study in a Rat Model of Dementia with Lewy Bodies

Abstract: Dementia with Lewy bodies (DLB) is characterized by neuronal deficits and α-synuclein inclusions in the brain. Ceftriaxone (CEF), a β-lactam antibiotic, has been suggested as a therapeutic agent in several neurodegenerative disorders for its abilities to counteract glutamate-mediated toxicity and to block α-synuclein polymerization. By using manganese-enhanced magnetic resonance imaging (MEMRI) and immunohistochemistry, we measured the effects of CEF on neuronal activity and α-synuclein accumulation in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…We reported a method of injection of Aβ and viral vectors with the SNCA gene into the brain to induce the DLB rat model (Lin et al, 2016). Consistent with our report (Ho et al, 2018), the present study revealed that DLB rats showed a high level of α-syn accumulation in the hippocampal DG and a lower density of pyramidal neurons in the hippocampal CA1 and DG.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We reported a method of injection of Aβ and viral vectors with the SNCA gene into the brain to induce the DLB rat model (Lin et al, 2016). Consistent with our report (Ho et al, 2018), the present study revealed that DLB rats showed a high level of α-syn accumulation in the hippocampal DG and a lower density of pyramidal neurons in the hippocampal CA1 and DG.…”
Section: Discussionsupporting
confidence: 94%
“…For avoiding high volume damage, rAAV and Aβ were not injected at a same brain area. Consistent to our previous report, we observed α-syn accumulation and cell loss in the hippocampus (Ho et al, 2018). These neurohistological changes were related to the behavioral defects in learning and recognition, which is consistent with literature reports showing that α-syn is involved in neurodegenerative synucleinopathies and in the onset and progression of DLB (Galvin et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, CEF might exert its neuroprotective actions through other mechanisms such as by affecting Aβ and tau protein metabolism and clearance in an AD model, prevent polymerization of α-synuclein in DLB (Ho et al, 2018) and PD (Ruzza et al, 2014;Tikhonova et al, 2018) models, which is of course, a call for further research to substantiate that the neuroprotective actions of CEF is also mediated via these important pathological proteins.…”
Section: The Possible Mechanism Of Actions Of Cef In Neurological Dismentioning
confidence: 99%
“…For instance, in animal models of Parkinson's disease, CEF exhibited a recovery of memory deficits (Huang et al, 2015), ameliorated abnormal uncontrolled movements (Chotibut et al, 2017), attenuated oxidative damage and restored the reduced levels of endogenous antioxidant enzymes (Bisht et al, 2014;Kaur and Prakash, 2017). Additionally, CEF modulated the expression of tyrosine hydroxylase (Chotibut et al, 2014), α-synuclein expression (Ho et al, 2018), and neuroinflammation (Kaur and Prakash, 2017) as well as prevented dopaminergic degeneration (Ho et al, 2014), while upregulating the levels of GLT-1 expression and glutamate uptake (Chotibut et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the molecular level, degradation of protein α synuclein leading to formation of Lewy bodies predominantly in the pars compacta of substantia nigra is the main hallmark of the disease (93)(94)(95). The formation of Lewy bodies is not privileged to Parkinson disease, but a group of disorders known as dementia with Lewy bodies is currently distinguished (96,97). The aggregation of Lewy bodies from α synuclein is not fully understood and probably abnormal degradation processes of the α synuclein, misfolding, acting of other proteins and enzymes, redox processes and phosphorylation take place in the pathology (98-100).…”
Section: Alzheimer Disease and The Other Neurodegenerationsmentioning
confidence: 99%